2020
DOI: 10.1111/jfs.12850
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of decontamination conditions for Aspergillus flavus inoculated to military rations snack and physicochemical properties with atmospheric cold plasma

Abstract: In this study, the effectiveness of ACP in inactivating Aspergillus flavus inoculated to military rations snack using response surface methodology (RSM) was investigated. Additionally, the effect of this treatment on the total count and yeast-mold count, as well as some quality properties of military rations snack, was examined. RSM was applied to study the voltage effects (5-15 kV), the distance between ACP emitter and sample (3-7 cm), and different treatment time (2-10 min) on the physicochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…ere are a few reports that have investigated the effect of cold plasma on lipid oxidation in nuts and nut products. Bagheri et al [28] reported an increment of peroxide values of military ration snacks by increase in the voltage of generating the plasma device. irumdas et al [34] indicated that plasma treatment of walnuts and peanuts at different powers and time intervals led to increase in the peroxide value (20%) of the samples.…”
Section: Malondialdehyde Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…ere are a few reports that have investigated the effect of cold plasma on lipid oxidation in nuts and nut products. Bagheri et al [28] reported an increment of peroxide values of military ration snacks by increase in the voltage of generating the plasma device. irumdas et al [34] indicated that plasma treatment of walnuts and peanuts at different powers and time intervals led to increase in the peroxide value (20%) of the samples.…”
Section: Malondialdehyde Determinationmentioning
confidence: 99%
“…Sen et al [4] also reported that population of A. flavus and A. parasiticus in hazelnut samples decreased by about 4 log after low pressure (LP) plasma treatment (100 W for 30 min). Bagheri et al [28] observed that A. flavus spores reduced after cold atmospheric plasma (15 V, 10 min, and 3 cm) treatment on contaminated military ration snack samples.Šimončicová et al [29] stated that cold plasma treatment duration of 180 s showed a remarkable reduction in A. flavus growth on agar medium and also observed changes in hyphae structure after plasma treatment durations of 60 s and 180 s. Suhem et al [30] investigated the inactivation effect of cold atmospheric plasma on A. flavus spores in both agar medium and brown rice cereal bars and found that plasma treatment (40 W for 25 min) significantly suppressed the fungi growth on both samples. ey observed that cold plasma treatment effectively damaged the fungi structure and broke the conidiophores and vesicles.…”
Section: Decontamination Effect Of Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold plasma is considered as a partially or fully ionized gas that consists of photons, ions, and free electrons, as well as atoms in their fundamental or excited states with a net neutral charge (Misra et al., 2016). In recent years, CP as a novel decontamination technology in food and biological sciences research has received increased attention (Bagheri et al., 2020). Among all the unique features of CP, the most important feature seems to be the microbial inactivation by reactive oxygen and nitrogen species (Bagheri & Abbaszadeh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Cold plasma is formed by microwave (MV), radio frequency (RF), direct current (DC), and alternating current (AC). It has been used in a variety of setups, including dielectric barrier, jet plasma, and corona discharges [12]. Among all the unique features of cold plasma, the most important feature seems to be the microbial inactivation by reactive oxygen and nitrogen species [13].…”
Section: Introductionmentioning
confidence: 99%